Two patients with eating disorders treated by naltrexone - Kmoch, Vladimir; Papezova, Hana; Yamamotova, Anna (Neuro endocrinology letters, 2009)
According to a recent literature review on the opioid mechanism in eating disorders, we found that there is increasing reason to re-examine the treatment potential of naltrexone. The endogenous opioid system belongs to the important modulators of food intake. The eating disorders share many traits with substance dependence models. We present two case histories of time-limited naltrexone therapy to show that, in clinical practice, individualized indication may contribute to short-term improvement and to prediction of a different long-term treatment outcome.
Keywords: narkotika - antagonisté; Narcotic Antagonists; naltrexon; afekt; Affect; Female; Adult; dospělí; Self-Assessment; Alcoholism; ženské pohlaví; sebezhodnocení (psychologie); Humans; poruchy příjmu potravy; lidé; alkoholismus; Naltrexone; Feeding and Eating Disorders